Organic synthesis using transition metals - Bates, Roderick (Chichester, West Sussex : Wiley, 2012)
"Organic Synthesis Using Transition Metals, 2nd Edition considers the ways in which transition metals, as catalysts and reagents, can be used in organic synthesis. It concentrates on the bond-forming reactions that set transition metal chemistry apart from "classical" organic chemistry"--
Cover; Title Page; Copyright; Dedication; About the Author; Preface; Chapter 1: Introduction; 1.1 The Basics; 1.2 The Basic Structural Types; 1.3 Just How Many Ligands Can Fit Around a Metal Atom?; 1.4 Mechanism and the Basic Reaction Steps; 1.5 Catalysis; Chapter 2: Coupling Reactions; 2.1 Carbon-Carbon Bond Formation; 2.2 Lithium and Magnesium: Kumada Coupling; 2.3 Zinc: The Negishi Reaction; 2.4 Aluminium and Zirconium; 2.5 Tin: The Stille Reaction; 2.6 Boron: The Suzuki Reaction; 2.7 Silicon: The Hiyama Reaction; 2.8 Copper: The Sonogashira Reaction; 2.9 Other Metals; 2.10 Homocoupling.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Transition metals; Organic compounds -- Synthesis; Transition metal complexes; SCIENCE -- Chemistry -- Industrial & Technical; Organic compounds -- Synthesis; Transition metals; Katalyse; Organische Synthese; Übergangsmetall.; Electronic books; Electronic books; Electronic books